Chronotypes, Sleep and Mental Distress Among Chinese College Students: A Cross-Sectional Study - Wang, Jiajia; Liu, Shuai; Guo, Junlong; Xiao, Rong; Yu, Jia; Luo, Xian; Xu, Yan; Zhao, Yuhan; Cui, Yingru; Gu, Yue; Cai, Lidan; Zhang, Bin (Frontiers in Psychiatry, 2022)
Objective: This study aimed to investigate the chronotypes and their relationship with sleep disturbances and mental distress among college students. Methods: Students from a university in Guangzhou, China, were recruited through a cross-sectional online survey. Data were collected by self-reported questionnaires including socio-demographics, lifestyles and health conditions, sleep patterns on weekdays and weekends, as well as the reduced Morningness-Eveningness Questionnaire (rMEQ), the Insomnia Severity Index, the Epworth Sleepiness Scale, the Beck Depression Inventory-13, and the Zung Self-Rating Anxiety Scale. Multivariate analyses were performed to examine the associations of chronotypes with sleep compensation, sleep disturbances, and mental distress. Results: A total of 1607 questionnaires were received, among which 1569 (97.6%) were valid for further analysis. Among these participants (mean age 19.86 ± 1.16 [15-27] years), morning types (M-types), intermediate types (I-types), and evening types (E-types) accounted for 14.9%, 71.5%, and 13.6%, respectively. The regression analysis revealed that E-types were positively associated with long sleep compensation on weekends (adjusted OR 2.443, 95%CI 1.740-3.429) compared with I-types, while M-types were the opposite (adjusted OR 0.623, 95%CI 0.392-0.990). E-types were also positively correlated with insomnia symptoms (adjusted OR 2.000, 95%CI 1.428-2.801), depressive symptoms (adjusted OR 2.068, 95%CI 1.496-2.858), and anxiety symptoms (adjusted OR 2.188, 95%CI 1.387-3.451). However, no significant association was found between chronotypes and excessive daytime sleepiness. Conclusion: Our study found that E-types were associated with long sleep compensation on weekends and insomnia, depression, and anxiety symptoms. Our findings emphasized the importance of early recognition and intervention of E-types and their accompanied sleep problems and mental distress.